EFEKTIVITAS SENAM MARYAM TERHADAP KECEMASAN IBU HAMIL TRIMESTER TIGA DI PUSKESMAS MANDALA - Iswanti, Tutik; Rohaeti, Ayi Tansah (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Anxiety and depression in pregnancy is a problem with a fairly high prevalence, which is around 12.5-42%, it is even estimated that this disorder will become the second largest cause of disease in 2020. Anxiety and depression in developed countries are around 7-20% and in developing countries around 7-20%. more than 20%. Maryam gymnastics is one of the non-pharmacological therapies, where Maryam exercises can affect the psychology of mothers, especially pregnant women who experience psychological changes due to pregnancy. The purpose of the study was to determine the effectiveness of Maryam exercise on the anxiety of pregnant women in the third trimester. The method used is Quasy Experiment with pretest and posttest, the number of samples is 31 respondents, the sampling technique that meets the inclusion criteria. The intervention method that will be carried out is that pregnant women in the third trimester with gestational age 28-33 weeks who have performed prenatal check-ups at least twice at the Health Service Facility will be intervened with maryam exercise three times a week for four weeks. Before the intervention, the respondent's level of anxiety was measured using a questionnaire and after the intervention for four weeks, the level of anxiety was measured again. Research analysis using Wilcoxon test. The results showed that the average anxiety in pregnant women before participating in Maryam's gymnastics was (75.92) which was much different from after participating in Maryam's gymnastics, which was (52.32). Here the 31 respondents experienced a decrease in anxiety with an average decrease of 16. The p value was obtained at 0.000 (p <0.05), which means that there is an effect of Maryam's exercise on the anxiety of pregnant women in the third trimester. Thus, Maryam's exercise can reduce anxiety in third trimester pregnant women.